Caring for Traditions Through the Madrasah Hidden Curriculum: An Offer from the Pekalongan City NU Community - Murodah, Nelli; Untung, Slamet; Abdul Aziz, Muhammad; Roja Badrus Zaman, Ahmad (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
This research is a qualitative study aimed at analyzing the implementation of the hidden curriculum at Madrasah Ibtidaiyah NU Buaran Pekalongan and identifying the obstacles encountered. Data were obtained through in-depth interviews, participatory observation, and documentation review. Data analysis was conducted using the interactive analysis model developed by Miles and Huberman. The results of the study indicate that three curricula are applied at Madrasah Ibtidaiyah NU Buaran Pekalongan, namely: 1) the national curriculum, 2) the Ministry of Religious Affairs curriculum, and 3) the pesantren curriculum. The pesantren curriculum, which is a hidden curriculum, is implemented in the takhassus classes at this madrasah. Takhassus classes offer learning programs that include Qur'an memorization (tahfidzul Qur'an), enjoyable language learning (language fun), basic study of classical Islamic texts (kitab kuning), TPQ (Qur'an learning for children), and outing class activities. Obstacles in Qur'an memorization, enjoyable language learning, basic study of classical Islamic texts, TPQ, and outing class activities are addressed with temporary (short-term) and permanent (long-term) solutions. Short-term solutions are applied to Qur'an memorization, basic study of classical Islamic texts, and outing class activities, while long-term solutions are applied to enjoyable language learning and TPQ. These solutions aim to preserve the traditions at Madrasah Ibtidaiyah NU Buaran Pekalongan through a hidden curriculum that continues to be maintained.